Pengaruh Model Pembelajaran Inkuiri Dengan Menggunakan Media Simulasi Terhadap Hasil Belajar Fisika Siswa Kelas X MIA SMAN 1 Lingsar Lombok Barat Tahun Pelajaran 2016/2017 - Suci Nujul Hayati; Hikmawati Hikmawati; Wahyudi Wahyudi (Department of Physics Education, Universitas Mataram, 2017)
This study aims to determine the effect of inquiry learning model using simulated media on learning outcomes physics class X SMAN 1 Lingsar Lombok Barat in the academic year 2016/2017. This kind of research is quasi experimental research design posttest control group design. Population of this research is all students in grade X SMAN 1 Lingsar the school year 2016/2017. Sample was taken by purposive sampling technique, in order to obtain class X mathematics and natural sciences 2 consisting of 25 students as an experimental class and class X mathematics and natural sciences 3 consisting of 24 students as the control class. Instruments in the form of multiple choice questions test which refers to the studentsÃ¢â¬â¢ cognitive abilities as many as 30 items with due regard to the validity, reliability, power and the level of difficulty depending matter. Based on the results obtained that the average value of 68,4 posttest experimental class and control class 58,75. Data obtained in advance were tested for normality and homogeneity, earned both classed of normally distributed and homogeneous. Research hypotheses were tested using t-test polled variance, obtained tcount and ttable by 2,98 and 2,01 at the 5% significance level. Therefore tcount > ttable then H0 is rejected and Ha accepted. So, it can be concluded that there are significant inqury learning model using simulated media on learning outcomes physics class X SMAN 1 Lingsar Lombok Barat lessons year 2016/2017.ÃÂ